Aspectos lingüísticos y culturales del español en la enseñanza de esta lengua a extranjeros - Carrera de la Red, Fátima; Sáinz García, Avelina (Wydawnictwo Naukowe UAM, 2001)
This article deals with the problem of teaching of Spanish language teachers and of some aspects o f the methodology o f teaching Spanish to foreigners. It contains results of experiments conducted by philology students at the Cantabria University in Santander (Spain) within the course of unconventional classes Teaching Spanish as a foreign language.
Linguistic and cultural aspects o f Spanish in teaching o f this language to foreigners